Quantitative and qualitative analysis of X-efficiency in the Croatian market - Ozren Rafajac; Marinko Skare (Contemporary Economics, 2017)
This article aims to explain the idea of X-efficiency, which indicates the difference between potential and actual output. If any business subject produces below its own potentials, it can be considered X-inefficient. To determine whether X-inefficiency in Croatian companies exists, how large it is in its volume and why it appears, in 2014, empirical research was conducted. Since only 22% of interviewed companies use all their available resources and given that the mean capacity utilization rate is only 70% and the mean resource utilization rate is 68%, our study results suggest that among business subjects in the Republic of Croatia, X-inefficiency exists to a large extent. Qualitative analysis shows that X-inefficiency appears mostly because of the competitive pressure. Other reasons include legal and administrative problems, the existence of inertness and a lack of motivation, the decision to work 'less for more', inadequate demand, economic crisis, the decision to save resources for future use, seasonal demand, incompetence of the government, corruption, and the risk of debt collection as well as local organizational problems.
Keywords: D61; G14; P2; P0; 330; X-efficiency; social efficiency; market failures; transitional economies